2011
DOI: 10.2147/jmdh.s17529
|View full text |Cite
|
Sign up to set email alerts
|

Societal costs and burden of otitis media in Portugal

Abstract: This study aimed to estimate the resource consumption and societal impact of otitis media (OM) in children younger than five years of age in Portugal. An Internet survey on generic childhood symptoms and diseases was administered to a sample of parents. This self-report survey had been previously implemented in other European countries. Medically confirmed OM was defined as symptoms of earache or “running ear” and/or a diagnosis of OM provided by a medical doctor. Direct medical, nonmedical, and indirect nonme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In our cohort, all patients had a physician diagnosis of AOM, and for most, a basic AOM-related examination, such as ear inspection and cleaning (including suction), was performed. A small proportion of children were hospitalized, and while most children received antibiotics, the relatively high rate of antibiotic use is similar to that reported in previous studies [ 3 , 14 , 26 , 27 ]. More intensive treatment (e.g., ventilation tube placement, hospitalization) was required as a consequence of AOM complications in a small number of both recurrent and non-recurrent AOM cases.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our cohort, all patients had a physician diagnosis of AOM, and for most, a basic AOM-related examination, such as ear inspection and cleaning (including suction), was performed. A small proportion of children were hospitalized, and while most children received antibiotics, the relatively high rate of antibiotic use is similar to that reported in previous studies [ 3 , 14 , 26 , 27 ]. More intensive treatment (e.g., ventilation tube placement, hospitalization) was required as a consequence of AOM complications in a small number of both recurrent and non-recurrent AOM cases.…”
Section: Discussionsupporting
confidence: 84%
“… EQ-5D EuroQoL-5 Dimension questionnaire a The Malaysian EQ-5D Index-based health state is scored between 0.131 (worst imaginable health state) and 1 (best imaginable health state) [ 26 ] b The EQ-5D Disutility Score is based on Shafie et al [ 25 ]; gender norms minus observed EQ-5D score. Lower scores are better …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, between AUD 100 and 400 million was spent in treating otitis media in 2008 [4], and USD 497 million was spent in South Korea in 2012 [5]. The estimated total costs for otitis media in Portugal were EUR 334 million in 2009 [6]. Apart from major financial costs internationally noted in treating otitis media, considerable physical, social and emotional burdens may be experienced by the affected children and their caregivers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pneumoniae , nontypeable Haemophilus influenzae, Moraxella catarrhalis , and Streptococcus pyogenes are the most common bacterial pathogens that cause AOM [ 2 ]. Several studies have shown that in recent years, even outside the pandemic period, incidence of AOM has declined worldwide [ 4 , 5 , 6 ]. In the USA, between 2011 and 2016 the annual incidence of AOM in children aged 0–9 years was reduced by about 25% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%